Ultrawide electrical tuning of light matter interaction in a high electron mobility transistor structure - Pal, Shovon (Sci Rep, 2015)
The interaction between intersubband resonances (ISRs) and metamaterial microcavities constitutes a strongly coupled system where new resonances form that depend on the coupling strength. Here we present experimental evidence of strong coupling between the cavity resonance of a terahertz metamaterial and the ISR in a high electron mobility transistor (HEMT) structure. The device is electrically switched from an uncoupled to a strongly coupled regime by tuning the ISR with epitaxially grown transparent gate. The asymmetric potential in the HEMT structure enables ultrawide electrical tuning of ISR, which is an order of magnitude higher as compared to an equivalent square well. For a single heterojunction with a triangular confinement, we achieve an avoided splitting of 0.52 THz, which is a significant fraction of the bare intersubband resonance at 2 THz.